Analisis Pengaruh Frekuensi Liar terhadap Sinyal Pancaran Localizer Frekuensi 109.1 MHz di Perum LPPNPI Cabang Yogyakarta - Ningrum, Ditha Sari Puspita (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2024)
The localizer at Perum LPPNPI Yogyakarta Branch uses the Normarc brand Type NM7013 with a working frequency of 109.1 MHz. One incident on September 12 2023, there was a report from the pilot stating that the signal from the Runway 09 localizer equipment received by the pilot was unstable. This research uses the fishbone diagram method and calculations and simulations of potential interference using dRSS, iRSS, and C/I parameters using SEAMCAT for predetermined distance samples. In addition, an analysis was carried out regarding the effect of interference on the localizer beam signal. The results of this research are that wild frequency interference with the localizer occurs at distances d3 (15 NM), d4 (20 NM), and d5 (25 NM). Meanwhile, interference does not occur at distance d1 (5 NM) and distance d2 (10 NM). The effect of this frequency interference is the disruption of the aircraft landing process at Adi Sutjipto Airport. To overcome these problems, air navigation service providers must ensure that the ILS system is properly maintained and protected from frequency interference.